EFFECTIVENESS OF DRYLAND TRAINING MODELS ON FREE STYLE SWIMMING FOR STRENGTH OF MUSCLE MUSCLE USING MODIFICATION OF ROWING TOOLS ”FOR CHILDREN AGED 13-15 YEARS - Akbar Ridwan Pambudi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
This study aims to make variations of exercise or physical activity using a modification of rowing equipment. Data collection was carried out in June 2019 which took place in the Nirwana Swimming Pool in Bogor District, and the yon zikon 13 of Lenteng Agung. This research method used research and development methods (Borg and Gall), compared 40 people from Pyramid S.C. athletes. The research process is preceded by observation and interviews. Taking the test is preceded by a pre-test that is taking 50m freestyle swimming time, then athletes are given assistance doing programmed physical activity using a modified paddle device, then Post-test takes 50m freestyle swimming time. The technique of collecting data before and after doing physical activity Then completed and analyzed using SPSS. T test results showed a significant effect on increasing swimming 50 m after physical activity using the dryland rowing exercise model. Pretest-post-test results with an average value of 1.05 and a control group with an average value of 0.17, this difference is the average value of increasing the speed of test results in groups. Selection of the mean results of the different values ​​of the experimental group and the control group or the average difference = 0.120 t-count = 1.049, df = 18, with p-value = 0.000 <0.05, it can be concluded that it is related to significant research between groups experiments and control groups, which means they have the "Effective" interpretation category. The importance of a significant difference in the dryland rowing exercise model in the freestyle before and now being given the freedom to use a modified rowing device, is undeniably the training model developed to increase the swimming speed of 50 m.